2014
DOI: 10.1111/saje.12063
|View full text |Cite
|
Sign up to set email alerts
|

Re‐Visiting Financial Development and Economic Growth Nexus: The Role of Capitalization inBangladesh

Abstract: This paper revisits the relationship between financial development and economic growth in Bangladesh by incorporating trade openness in production function using quarter frequency data over the period of 1976-2012. We applied combined Bayer-Hanck cointegration to examine cointegration amongst variables in the presence of structural breaks. The results show that financial development facilitates economic growth but capitalization impedes it. In addition, trade openness stimulates economic growth. Labour is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 109 publications
3
37
0
2
Order By: Relevance
“…Financial innovation introduces and popularizes new financial instruments, institutions, and technologies to the financial system (Sood and Ranjan 2015). Schumpeter (1911) emphasized the importance of well-functioning financial intermediaries in innovation and economic growth. The interactions of innovations in the financial sector create economic growth.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial innovation introduces and popularizes new financial instruments, institutions, and technologies to the financial system (Sood and Ranjan 2015). Schumpeter (1911) emphasized the importance of well-functioning financial intermediaries in innovation and economic growth. The interactions of innovations in the financial sector create economic growth.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Innovation not only considers the creation of a new thing but also acts as the panacea for prolonged economic problems (Kotsemir and Abroskin 2013). Schumpeter (1912) indicated that innovation can take place in the form of a new product, process, market, raw material, a method of distribution, or organizational structure.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…For example, (Claessens & Laeven, 2003) show that financial development contributes to economic growth. They share the share the view with many authors who agreed that financial development causes economic growth ,see ( Shahbaz, Rehman, & Muzaffar, 2015;Sehrawat & Giri, 2012;Shahbaz & Mafizur Rahman, 2014;Anwar & Sun, 2011). Masoud & Hardaker (2012) emphasized that stock market development (as part of financial development) has a significant effect on economic growth.…”
Section: Literature Reviewmentioning
confidence: 76%
“…According to R. King & Levine (1993), at the cross-country level, evidence indicates that various measures of financial development (including assets of the financial intermediaries, liquid liabilities of financial institutions, domestic credit to private sector, stock and bond market capitalization) are robustly and positively related to economic growth. Shan, Morris, & Sun (2001) also said that there is little support for the hypothesis that finance "leads" growth, and caution must be exercised in making general conclusions about this relationship. Rousseau & D'Onofrio (2013) found unidirectional links from financial development to measures of real activity for about twothirds of Sub Saharan African countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, most countries have begun to implement various policies in order to reduce the share of the shadow economy and in turn raise their total tax revenues. In this context, improvements in the financial sector have a potential to affect the tax collection positively by affecting the economic activity positively (See Shahbaz et al, 2015;Caporale et al, 2015;and Peia and Roszbach, 2015) and decreasing the shadow economy. In this paper, we investigated the impact of improvements in both the banking sector and stock market on tax revenues.…”
Section: Financial Development and Tax Revenues In Turkey: A Non-linementioning
confidence: 99%